Loss of hepatic Mboat7 leads to liver fibrosis. Issue 5 (26th June 2020) - Thangapandi, Veera Raghavan; Knittelfelder, Oskar; Brosch, Mario; Patsenker, Eleonora; Vvedenskaya, Olga; Buch, Stephan; Hinz, Sebastian; Hendricks, Alexander; Nati, Marina; Herrmann, Alexander; Rekhade, Devavrat Ravindra; Berg, Thomas; et al.
Abstract : Objective: The rs641738C>T variant located near the membrane-bound O-acyltransferase domain containing 7 (MBOAT7) locus is associated with fibrosis in liver diseases, including non-alcoholic fatty liver disease (NAFLD), alcohol-related liver disease, hepatitis B and C. We aim to understand the mechanism by which the rs641738C>T variant contributes to pathogenesis of NAFLD. Design: Mice with hepatocyte-specific deletion of MBOAT7 (Mboat7 Δhep ) were generated and livers were characterised by histology, flow cytometry, qPCR, RNA sequencing and lipidomics. We analysed the association of rs641738C>T genotype with liver inflammation and fibrosis in 846 NAFLD patients and obtained genotype-specific liver lipidomes from 280 human biopsies. Results: Allelic imbalance analysis of heterozygous human liver samples pointed to lower expression of the MBOAT7 transcript on the rs641738C>T haplotype. Mboat7 Δhep mice showed spontaneous steatosis characterised by increased hepatic cholesterol ester content after 10 weeks. After 6 weeks on a high fat, methionine-low, choline-deficient diet, mice developed increased hepatic fibrosis as measured by picrosirius staining (p < 0.05), hydroxyproline content (p < 0.05) and transcriptomics, while the inflammatory cell populations and inflammatory mediators were minimally affected. In a human biopsied NAFLD cohort, MBOAT7 rs641738C>T was associated with fibrosis (p = 0.004) independent of the presence of histological inflammation. Liver lipidomes of Mboat7 Δhep mice and human rs641738TT carriers with fibrosis showed increased total lysophosphatidylinositol levels. The altered lysophosphatidylinositol and phosphatidylinositol subspecies in MBOAT7 Δhep livers and human rs641738TT carriers were similar. Conclusion: Mboat7 deficiency in mice and human points to an inflammation-independent pathway of liver fibrosis that may be mediated by lipid signalling and a potentially targetable treatment option in NAFLD.